2019
DOI: 10.1542/peds.2018-2554
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Influencer Marketing and Children’s Food Intake: A Randomized Trial

Abstract: OBJECTIVES: To examine the impact of social media influencer marketing of foods (healthy and unhealthy) on children's food intake. METHODS:In a between-subjects design, 176 children (9-11 years, mean 10.5 6 0.7 years) were randomly assigned to view mock Instagram profiles of 2 popular YouTube video bloggers (influencers). Profiles featured images of the influencers with unhealthy snacks (participants: n = 58), healthy snacks (n = 59), or nonfood products (n = 59). Subsequently, participants' ad libitum intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
195
1
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(248 citation statements)
references
References 49 publications
(58 reference statements)
6
195
1
21
Order By: Relevance
“…Social learning theory claims that children's liking of a character increases the probability of imitating the character's action. Consistent with this, a previous study showed that exposure to Instagram posts of vloggers pictured with HFSS foods increased children's (9‐11 y) later consumption of HFSS products, compared with children in a control condition …”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Social learning theory claims that children's liking of a character increases the probability of imitating the character's action. Consistent with this, a previous study showed that exposure to Instagram posts of vloggers pictured with HFSS foods increased children's (9‐11 y) later consumption of HFSS products, compared with children in a control condition …”
Section: Introductionsupporting
confidence: 72%
“…Consistent with this, a previous study showed that exposure to Instagram posts of vloggers pictured with HFSS foods increased children's (9-11 y) later consumption of HFSS products, compared with children in a control condition. 15 Studies exploring the effect of celebrity endorsements of HFSS foods show that they can increase children's preferences, requests for, and intake of these products. [16][17][18] One study looked at effects on children's (aged 8-11 y) brand choice and intake by simultaneously offering children the endorsed brand and a perceived alternative brand and allowing them to choose the amount they consumed from each.…”
mentioning
confidence: 99%
“…In a recent study, when children (9-11 years) were exposed to influencer marketing of unhealthy foods via YouTube, they consumed significantly more of the marketed snack relative to the alternative brand [32], demonstrating a brand-specific effect that was not tempered by the presence of a disclosure informing children that they were viewing marketing content. When the exposure was to influencer marketing via Instagram, a non-specific effect on intake was found whereby children consumed almost 100 kcal more than the control group at a subsequent snack opportunity where the marketed foods were not available [33]. This is consistent with the beyond-brand consumption effects seen for television food advertising [34,35].…”
supporting
confidence: 66%
“…The male YouTuber had a subscriber count of approximately 11 million across his three YouTube channels, and the female YouTuber a total of 16 million subscribers across her two YouTube channels. The YouTubers' viewer demographics are not publicly available but they are known to be popular with children (5-15 years) in the UK [73] and are consistent with those used in previous experimental studies investigating the extent, nature and impact of influencer food marketing [14,22,23]. Notably, the influencer marketing campaign shown was featured in content likely to be viewed by children, and not in content specifically targeted at them (e.g., YouTube Kids app), where self-regulation should prohibit exposure [74].…”
Section: Youtube Video Featuring Influencer Marketingmentioning
confidence: 75%
“…This may indicate that earlier theories of advertising, such as the persuasion knowledge model [47] which asserts that young children (12 years and under) are less able than adults to activate persuasion knowledge and so resist the effects, are perhaps outdated. However empirical research shows that advertising awareness alone has no protective effect on children's appetitive response to digital marketing of HFSS foods [56][57][58][59] or more specifically influencer marketing of these foods [22,23]. This is likely because children under the age of 12 are unlikely to apply advertising knowledge while being exposed to an advertisement, unless they are overtly made aware of the persuasive intent [51].…”
Section: Theme 6: Children Feel Able To Resist Influencer Marketing Omentioning
confidence: 99%